Decursinol-mediated antinociception and anti-allodynia in acute and neuropathic pain models in male mice: Tolerance and receptor profiling - Crawford, LaTaijah C.; Kim, Sangyub; Karelia, Deepkamal; Sepulveda, Diana E.; Morgan, Daniel J.; Lü, Junxuan; Henderson-Redmond, Angela N. (Frontiers in Pharmacology, 2022)
Previous studies by Korean scientists have shown that oral administration of Angelica gigas Nakai (AGN) root alcoholic extract and the metabolite of its pyranocoumarins, decursinol, have antinociceptive properties across various thermal and acute inflammation pain models. The objectives of this study were 1) to assess whether tolerance develops to the antinociceptive effects of once-daily intraperitoneally administered decursinol (50 mg/kg) in acute thermal pain models, 2) to establish its anti-allodynic efficacy and potential tolerance development in a model of chemotherapy-evoked neuropathic (CENP) pain, and 3) to probe the involvement of select receptors in mediating the pain-relieving effects with antagonists. The results show that decursinol induced antinociception in both the hot plate and tail-flick assays and reversed mechanical allodynia in mice with cisplatin-evoked neuropathic pain. Tolerance was detected to the antinociceptive effects of decursinol in the hot plate and tail-flick assays and to the anti-allodynic effects of ducursinol in neuropathic mice. Pretreatment with either the 5-HT2 antagonist methysergide, the 5-HT2A antagonist volinanserin, or the 5-HT2C antagonist SB-242084 failed to attenuate decursinol-induced antinociception in the tail-flick assay. While pretreatment with the cannabinoid inverse agonists rimonabant and SR144528 failed to mediate decursinol-induced anti-allodynia, pretreatment with the opioid antagonist naloxone partially attenuated the anti-allodynic effects of decursinol. In conclusion, our data support decursinol as an active phytochemical from AGN having both antinociceptive and anti-allodynic properties. Future work warrants a more critical investigation of potential receptor mechanisms as they are likely more complicated than initially reported.